The Voice of Geber (Lam 3) in the Panorama of Speaking Voices in the Book of Lamentations - Korzec, Cezary (The Biblical Annals, 2021)
The present study, acknowledging the centrality of Lam 3 in the book of Lamentations, examines the development of the speaking voice of the geber in this chapter and compares it with other voices speaking in the book. The questioned identity of the geber becomes a model for other ‘voices’: the narrator and the Daughter of Zion. The destruction of the city, carried out by God himself, indicates an exhaustion of the old institutions and the need for a new identity of both the Daughter of Zion and the supporters of the community of the city (i.e., the narrator) in the days of crisis.